ISSUES OF IMPROVEMENT OF THE INSTITUTION OF ADVOCACY IN CRIMINAL PROCEEDINGS - Tulaganova, Gulchehra (Antis Publisher, 2024)
In this article, suggestions were made regarding the issues of improving the legal profession, providing legal services by lawyers, and adding a new clause to the points where the participation of a lawyer is mandatory. It was also recommended that we move to the digitization of criminal proceedings at every stage, and that lawyers in our country continuously expand the use of electronic technologies in their activities. Also, the experience of some foreign countries was studied and many discussions were held. Recommendations were also made regarding the development of new legal bases of electronic criminal proceedings.